Thermodynamics Analysis on Methane Hydrate Formation in Porous Carbon - nandari, Wibiana W; Prasetyo, Imam; Fahrurrozi, Moh. (ASEAN Journal of Chemical Engineering, 2016)
Methane is a potential alternative energy source which is abundant and produces lower CO2 emissions when it is used as fuel due to the content of C in the methane molecule is much lesser than its H content. Besides in a form of gas, methane in nature can also be in the form of methane hydrates. The formation process of methane hydrates in nature can be adopted as a method of storage of methane. In this study, a thermodynamics review will be studied related to temperature and pressure in a phase equilibrium system of methane hydrate . Thermodynamic model aims to predict the stability of methane hydrates for effective storage of methane. Each volume of methane hydrate contains as 164 volumes of methane gas under standard conditions ( STP ). The study was conducted by adsorbing methane on a wet porous carbon with the method of static volumetric.. The experimental results show that at the temperature of 274 K methane hydrates was formed at a pressure of 2.75 MPa; at a temperature of 275 K, pressure of 3.16 MPa; at a temperature of 276 K, pressure of 3.44 MPa, while at a temperature of 277 K, pressure of 3.67 MPa. Temperatures and pressures data are used to calculate the parameters of Langmuir equation constants modeled by the Van der Waals - Platteeuw for the chemical potential of water in the hydrate phase, Holder et al for the chemical potential of water in the liquid phase, as well as for the Gibbs-Thomson effect of porous carbon media.